Penerimaan Teknologi Radio-Frequency Identification (RFID) di Plaza Tol dalam Kalangan Pengguna Jalanraya di Lembah Klang - Samsuddin, Siti Nurnadiah; R. Chandrashekar,; Salahudin, Shahrul Nizam (Research in Management of Technology and Business, 2020)
Malaysia has coordinated the use of toll electronically at all plaza toll plots available in Malaysia. This is to facilitate further payment of toll payments and to further demonstrate the rapid development of technology in the globalization era. This is also due to the increasing number of vehicles resulting in traffic congestion and road accidents arising from problems in the toll plaza. Therefore, Malaysia has introduced another new technology to facilitate and further roll out toll payments namely Radio Frequency Identification (RFID). This study aims to identify factors that influence the acceptance of RFID technology at the toll plaza in the Klang Valley. In addition, this study was conducted to identify the level of desire to use RFID technology in the toll plaza among road users in the Klang Valley. Data analysis was obtained through surveys. Data is collected from road users and the Expressway in the Klang Valley. The data analysis tool used is the Statistical Package for Social Science (SPSS). The findings are that road users in the Klang Valley are ready and comfortable receiving RFID technology at Toll Plaza.